Hagiografia i censura: el cas del Llibre de la vida i miracles de santa Madrona, i dels sants Celdoni i Armenter, de Salvador Pons (1594). - LLOPIS, CARME ARRONIS (Scripta, 2023)
This paper analyzes the withdrawal from sale, ordered by the Bishop of Barcelona Joan Dimes Lloris, of a hagiographic work, Llibre de la vida y miracles de santa Madrona, cos sant de Barcelona, i dels sants Celdoni i Armenter, cossos sants de Cardona, written by the Dominican Salvador Pons and published in 1594. This prohibition has been scarcely attended, and it has been explained as a problem inherent to the venerations addressed, considering that they were not recognized saints in the official Church, or related to the devout practices described in the text, considered as popular. However, in the article, I identify other specific aspects present in the text that had not been noted as problematic, and that were usual cause of prohibition of devout works, such as the inclusion of apocryphal content, that is, taken from unknown sources, in the construction of the narratives. This particular is relevant, since the book was written in a period of full effervescence in the rewriting of local hagiographic material, in order to prove the authenticity of the cults with criteria of authority and historicity.